The Fry Chronicles : An Autobiography - Fry, Stephen (London Penguin Books, 2010)
Stephen Fry is not just a multi-award-winning comedian and actor, but also an author, director and presenter. He is one of the most influential cultural forces in the country. This title details some of the most turbulent and least well known years of his life.
Include Illustrations and Index.
An Autobiography.
Keywords: Comedians -- Fry, Stephen, 1957- -- Television personalities